2016
DOI: 10.1097/mbc.0000000000000390
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation factor VIII, IX and XI levels in north Indian patients with venous thromboembolism

Abstract: Studies have shown elevated levels of certain coagulation factors as risk factors for venous thromboembolism (VTE). In this study, we investigated the levels of coagulation factor VIII (FVIII), FIX and FXI in north Indian patients with VTE. A total of 123 patients with VTE were screened prospectively for FVIII, FIX and FXI levels and the conventional risk factors - deficiencies of protein C, S and antithrombin, positivity for antiphospholipid antibodies and the factor V Leiden mutation. Age-matched and sex-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(37 reference statements)
1
3
1
Order By: Relevance
“…Five patients had a PS deficiency (10%), and three patients were deficient for AT (6%). The incidence of antiphospholipid antibodies among Indian patients with venous thrombosis ranges from 5.5 to 10% [3,[13][14][15] The present study also had similar incidence (4 cases; 8%). The presence of antiphospholipid antibodies among 6% (3 controls) of controls is uncommon.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Five patients had a PS deficiency (10%), and three patients were deficient for AT (6%). The incidence of antiphospholipid antibodies among Indian patients with venous thrombosis ranges from 5.5 to 10% [3,[13][14][15] The present study also had similar incidence (4 cases; 8%). The presence of antiphospholipid antibodies among 6% (3 controls) of controls is uncommon.…”
Section: Discussionsupporting
confidence: 77%
“…However, the incidence was less among can-Americans and other non-Caucasians [11]. Studies done in the Indian population with venous thrombosis reported the incidence of FVL mutation ranging from 3 to 12% of the patients [3,12,13]. In the present study, FVL mutation was seen in 5 patients (10%) and all were heterozygous.…”
Section: Discussioncontrasting
confidence: 37%
“…Fig. 3 shows the analysis of FVIII per 10 IU/dl categories, performed in the seven studies noted above and in five other published case-control studies [ 12 , 23 26 ]. The pooled odds ratio of VTE was 1.11 (1.07, 1.14).…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies were used for the OR estimates of the first VTE, containing data on 1,381 antithrombin-deficient individuals and 31,111 controls. 14,15,[17][18][19][21][22][23][24][25][26][27][28][29][31][32][33][34][35] Antithrombin-deficient individuals have an increased risk of a first VTE event as compared with controls, OR 14.0; 95% CrI, 5.5 to 29.0. An increased risk was found for antithrombin deficient individuals in all meta-analyses of subgroups of studies.…”
Section: First Vtementioning
confidence: 99%